Buying Behaviour of Consumers towards the Products Produced by SSM Units - Giram, Shivkumar J. (Indian Journal of Marketing, 2004)
Every producer, either of SSI unit or Big-unit manufactures products for sale .In order to capture the market for their product, the producer has to take efforts to attract the consumers towards their products. Moreover, to attract the consumer, it is essential to understand the buying behavior of the consumer, his requirements, expectations, and satisfaction and apply adequate marketing strategies accordingly.SSI units generally manufacture consumable products or consumable durable products. Generally such products includes-milk and milk products, bread, papad, potato chips, farsaan, honey, pickles, chilly powder, spices, detergent soaps, powder, paints, sanitary cleaning products, plastic products like-pipes, fixtures, water tanks, nylon ropes etc., steel furniture, electrical products like-bulbs, chokes, wires etc. Big companies on mass scale production, maintaining their quality standard, also manufacture all these products.